Enhancing safety in the ischaemic and haemorrhagic stroke population: exploring the efficacy of self-releasing chair alarm belts - Justin Weppner; Alaric Gee; Kevin Mesina (BMJ Open Quality, 2024)
Introduction A quality improvement study evaluated the effectiveness of implementing self-releasing chair alarm belts in an inpatient rehabilitation facility (IRF) for patients who had a stroke. The objective of this study is to assess the effectiveness of self-releasing chair alarms as a chair-level fall preventive tool in patients who had a stroke in the IRF setting.Methods A preintervention and postintervention quality improvement study was conducted in an IRF to address the high rate of falls in the stroke population. Falls from wheelchairs were identified as a significant concern, leading to the implementation of self-releasing safety belts (Posey HeadStart Notification Sensor Belts) with alarm systems as an intervention. In the preintervention phase (July 2021 to January 2022) falls from chairs while on standard fall precautions were recorded to establish a baseline. In the intervention phase, the self-releasing chair alarm belts were introduced along with standard fall precautions. The postintervention phase spanned from February 2022 to July 2022.Results In the preintervention phase, 20 out of 86 stroke subjects experienced a total of 30 falls from chairs. However, in the postintervention phase, only one subject experienced a fall from a chair out of 104 stroke subjects. The mean percentage of subjects involved in falls decreased from 24±11.4% to 1±0.4% (p<0.00001), and the mean fall rate per 1000 patient days declined from 4.6±2 to 0.2±0.1 (p<0.0001).Conclusions The implementation of self-releasing chair alarm belts significantly reduced falls from chairs among patients who had a stroke in the IRF setting. These findings highlight the effectiveness of this intervention in improving patient safety and fall prevention in IRFs.